Purpuric lesion in a patient with leprosy: Was it a Lucio’s phenomenon or an epiphenomenon? - Menaldi, Sri Linuwih; Marissa, Melani; Chairista, Inadia Putri; Lim, Henry W.; Rihatmadja, Rahadi (UI Scholars Hub, 2020)
Background: Lucio’s phenomenon (LP) is a severe necrotizing cutaneous reaction that occurs in patients with Lucio’s leprosy. The exact pathomechanism is not fully understood, but typically abundant acid-fast bacilli in the walls of blood vessels point to direct perturbation of blood supply to the epidermis. We report a case of LP where epidermal necrosis occurred in the absence of vascular invasion by mycobacteria, raising the question whether this was an epiphenomenon or a true LP. Case Illustration: A 34-year-old male was referred for an episodic swelling of his hands and feet that persisted for two years. There were signs of leprosy (diffuse shiny skin lesions, anesthesia, and anhidrosis of the extremities) with purpuric patches on lower extremities. The slit-skin smear test revealed a high index of acid- fast bacilli. Histopathological examination revealed epidermal necrosis and leukocytoclastic vasculitis without demonstrable bacillus. WHO multidrug regimen for leprosy and corticosteroids successfully cured the patient and prevented ulcer development. Discussion: Despite the presence of classical LP characteristics clinically and histologically, mycobacterium was absent in the vessels’ walls. We hypothesized that, in LP, vascular impairment might also be secondary due to antigen–antibody reaction and hypercoagulable state.Conclusion: Purpuric patches in Lucio’s leprosy might be the first sign of skin necrosis or vascular damage (purpura and ulceration). Besides the antimycobacterial drugs, anti-inflammatory drugs should be administered. Laboratory test for hemostasis might be advised.